Effect of Yogurt and Bifidobacterium on Cryptosporidium parvum Infection In Experiential Infected Mice - S.T. Mohammed; K. Jabur; H.A. Aja (Ibn Al-Haitham Journal for Pure and Applied Sciences, 2017)
This study aimed to collected 150 feces sample from calves suffering sever diarrhea ,then there were isolation and purification of Cryptosporidium parvum oocyst from samples contain it. These oocysts were used to induce experimental infection in the Immunosupperessed mice, then the mice treated by Bifidium bacteria , its supernatant and local yogurt were used for bacterial isolation.